Wirtschaftswerte / Museumswerte. - Jansen, Gregor; Bergmann, Dana; Kunsthalle Düsseldorf, Düsseldorf (Köln : Verlag der Buchhandlung Walther König, 2017)
Broodthaers, Marcel ; Richter, Gerhard ; Dimitrijević, Braco ; Roth, Dieter ; Anselmo, Giovanni ; Long, Richard ; Kounellis, Jannis ; Christo ; Cragg, Tony ; Warhol, Andy ; Dine, Jim ; Feldmann, Hans-Peter ; Klein, Yves ; Fontana, Lucio ; Knoebel, Imi ; Haacke, Hans ; Flaganan, Barry ; Buren, Daniel ; Panamarenko ; Art & Language ; Bernd & Hilla Becher ; Palermo, Blinky ; Beuys, Joseph ; Darboven, Hanne ; Lohaus, Bernd ; Paik, Nam June ; Gilbert & George ; Geys, Jef ; Kawara, On ; Venlet, Richard
Wirtschaftswerte / Museumswerte, Kunsthalle Düsseldorf, Düsseldorf, 8. April - 18 Juni 2017
boek